Characterisation of building exposure to wind-driven rain in the UK and evaluation of current standards. Issue 180 (September 2018) - Orr, Scott Allan; Viles, Heather
Abstract: One method of estimating WDR exposure is semi-empirical formulae based on hourly meteorological data including ISO 15927–3:2009 and BS 8104:1992. These provide protocols to estimate extreme WDR exposure, such as the worst spell likely to occur in any given three-year period. This study characterises the amount of annual WDR exposure and the frequency and duration of directional WDR spells for eight sites in the UK from 1986 to 2015. To assess the utility of these standards for evaluating extreme WDR exposure at those sites, the worst spell likely to occur in any given three-year period is determined using a 'return period' approach from extreme value analysis (EVA). It is shown that in the context of the prevailing wind patterns in the UK wall orientation is an important factor in determining the frequency and duration of WDR spell properties. EVA is applied for eight sites in the UK from 1959 to 1991 to evaluate the methods and climatic data used in BS 8104:1992 and their relevance to current climate. Both standards underestimate the volumetric exposure of the 'once every three years' spell compared to EVA for methodological reasons but are useful tools to assess annual exposure and compare between sites. Highlights: Recent annual and 'once every three year' WDR exposure is assessed for 8 UK sites. Wall orientation strongly influences frequency and duration of WDR spells in the UK. ISO 15927 and BS 8104 underestimate extreme WDR compared to extreme value analysis.